Meta-analysis of the potential role of extracorporeal shockwave therapy in osteonecrosis of the femoral head - Yangquan Hao; Hao Guo; Zhaochen Xu; Handeng Qi; Yugui Wang; Chao Lu; Jie Liu; Puwei Yuan (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background We aimed to evaluate the role of extracorporeal shockwave therapy (ESWT) in improving osteonecrosis of the femoral head (ONFH). Methods We searched studies focusing on the role of ESWT in ONFH using PubMed, Embase, the Cochrane Library, WanFang, VIP, and CNKI databases updated up to July 28, 2017, without language restriction. Standardized mean difference (SMD) values and 95% confidence intervals (95% CIs) were pooled to compare the pain score and Harris hip score for ESWT treatment and other treatment strategies. Results Four articles, including 230 ONFH patients, were eligible for the meta-analysis. No significant differences were found in the pain score (SMD = − 1.0104; 95% CI − 2.3279–0.3071) and Harris hip score (SMD = 0.3717; 95% CI − 0.3125–1.0559) between the two groups before treatment. After treatment, significant differences were found between the experimental and control groups in the pain score (SMD = − 2.1148; 95% CI − 3.2332–0.9965) and Harris hip score (SMD = 2.1377; 95% CI 1.2875–2.9880). There were no significant differences in pain score before and after treatment between the two groups (SMD = − 0.7353; 95% CI − 2.1272–0.6566), but significant differences were found in the Harris hip score (SMD = 1.2969; 95% CI 0.7171–1.8767). Conclusion For patients at an early stage, ESWT may be safe and effective for relief of pain and improvement of motor function.